Les mauvaises herbes : ennemies ou alliées ? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Les plantes adventices sont redoutées des agriculteurs du monde entier qui les considèrent, souvent